Impact of Different Scan Bodies and Scan Strategies on the Accuracy of Digital Implant Impressions Assessed with an Intraoral Scanner: An In Vitro Study. Issue 4 (16th December 2019) - Motel, Constantin; Kirchner, Elena; Adler, Werner; Wichmann, Manfred; Matta, Ragai Edward
Abstract: Purpose: Sufficient data are not currently available on how the various geometries of scan bodies and different scan strategies affect the quality of digital impressions of implants. The purpose of this study was to present new data on these two topics and give clinicians a basis for decision making. Materials and Methods: A titanium master model containing three Nobelreplace Select™ implants (Nobelbiocare Services AG, Zurich, Switzerland) was digitized using an ATOS industrial noncontact scanner. Digitization was repeated three times with different types of scan bodies integrated into the implants: ELOS A/S, nt‐trading GmbH, and TEAMZIEREIS GmbH. These three scans served as virtual master models. The titanium master model was then scanned with the TRIOS3© digital intraoral scanner (ELOS A/S, Copenhagen, Denmark), which was used for two different scanning strategies. Strategy A was a one‐step procedure that included both the titanium master model and the integrated scan bodies. Strategy B comprised two steps. First, a digital overlay was performed with a scan of the titanium master model without integrated scan bodies. A second scan was performed with the titanium master model and integrated scan bodies. By repeating both strategies 10 times for each type of scan body, 60 scans were generated and the corresponding standard tessellation language data sets overlaid with the corresponding virtual master model. Deviations in the resulting superimpositions were calculated and evaluated separately in the individual axes (x, y, z) and in three‐dimensional space (Euclidean distance). Statistical evaluation was performed using the R‐project software. Level of significance was determined at p ≤ 0.05. Results: With regard to the geometry of the scan bodies, strategy A significantly influenced the accuracy of the digital implant impression in regards to Euclidean distance ( p = 0.003). No significant difference was found for strategy B in this context. Comparing the two scan strategies revealed that strategy A achieved significantly higher accuracy overall ( p = 0.031). Conclusion: The quality of digital intraoral impressions seems to be influenced by both the geometry of the scan body and the scan strategy. For clinical practice, the one‐step scan strategy seems beneficial. Furthermore, the scan bodies of ELOS A/S showed a potential clinical advantage.